Comparing dualised forms of initial VET across countries : Insights from the IEM survey - Le Mouillour, Isabelle [Verfasser]; Neff, Daniel [Verfasser]; Klein, Paula [Verfasser] (My University, 2023)
"Worldwide, the importance of dualised forms of initial vocational education and training is increasing. Within the EU, in particular the high youth unemployment in parts of Europe has led to an increased interest in more practice-integrated initial VET. This has led to an introduction of new and expansion and/or modernization of existing apprenticeship schemes across the EU over the last decade (Cedefop und OECD 2021). Due to this relatively recent development, there are few systematic overviews of existing and new training programs with company-based components and only a few efforts to classify/typify this diversity (e.g. Markowitsch und Wittig 2020). The present paper aims to add to the literature through an exploratory analysis based on the BIBB International Expert Monitor survey on dualised forms of IVET firstly conducted in 2021/22. The expert survey was specifically designed to capture and monitor dualised forms of IVET over time. The analysis firstly provides an overview of dualised forms of IVET across the sampled countries based on a clear definition of dualised forms of IVET. It then moves on to explore similarities and differences between the countries on the basis of five selected indicators of attractiveness of dualised forms of IVET. Lastly, an analysis of the reported developments over time (in the past five years) is undertaken. One notable example is the Cedefop European database on apprenticeship schemes." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; T 3.4 Befragung; I 2.2 Europa; 370; Berufsbildungssystem; Duales System; Betriebliche Berufsausbildung; Lernen am Arbeitsplatz; Modernisierung; Typologie; Expertenbefragung; Quantitative Angaben; Internationaler Vergleich; Europa